Migration = Cloning ; Aliasing (Preliminary Version) - Hüttel, Hans; Kleist, Josva; Nestmann, Uwe; Merro, Massimo (BRICS Report Series, 1998)
In Obliq, a lexically scoped, distributed, object-based programming language, object migration was suggested as creating a (remote) copy of an object’s state at the target site, followed by turning the (local) object itself into an alias, also called surrogate, for the just created remote copy. There is no proof that object migration in Obliq is safe in any sense. We consider the creation of object surrogates as an abstraction of the above-mentioned style of migration. We introduce Øjeblik, a distribution-free subset of Obliq, and provide two formal semantics, one in an intuitive configuration style, the other in terms of pi-calculus. The intuitive semantics shows why surrogation is neither safe in Obliq, nor can it be so in full generality in Repliq (a repaired Obliq). The pi-calculus semantics allows us to prove that surrogation in Øjeblik is safe for certain well-identified cases, thus suggesting that migration in Repliq may be safe, accordingly.